Preparation of Sonocatalyst Fe2O3/ZnO using Sol-gel/precipitation method: characterization and removal of acid orange 7 in aqueous solution / Nur Fadzeelah A. K. and Nor Aimi Abdul Wahab - Abu Kassim, Nur Fadzeelah; Abdul Wahab, Nor Aimi (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Fe2O3/ZnO composite catalyst was synthesized using a solgel/precipitation method. The synthesized samples were characterized by Xray diffraction (XRD), scanning elctron microscope (SEM) with energy dispersive X-tray spectroscopy (EDX) and Brunauer−Emmet−Teller (BET) method. The feasibility of Fe2O3/ZnO composite catalyst on the removal of Acid Orange 7 (AO7) solution was examined under an ultrasonic irradiation. The removal percentage of AO7 solution was monitored by UVvis spectrophotometer. The characterization results exhibited that the Fe2O3/ZnO composite catalyst was successfully prepared using the solgel/precipitation method. The loading of Fe2O3 particles on the surface of ZnO particles resulted in high surface area compared to ZnO catalyst. Performance wise, the highest removal percentage of AO7 solution for sonocatalytic activity (at 120 min) showed only 8.05% and 9.12% for ZnO catalyst and Fe2O3/ZnO composite catalyst, respectively. Thus, the poor removal of AO7 solution in sonocatalytic experiment using this composite catalyst indicating this catalyst is not a good potential as sonocatalyst in treatment of azo dyes. In addition, this study has revealed that Fe2O3/ZnO composite catalyst was superior to the adsorption activity in removing of AO7 from aqueous solution due to adsorption ability of Fe2O3.